Peranan Orangtua Terhadap Penggunaan Media Sosial Anak dibawah Umur - Aura Doa Apriliansyah; Raihani Firdaus; Zulfa Saniyyah (Kampret Journal, 2022)
The emergence of social media is one of the developments of the entry of globalization which makes humans connected to each other. With descriptive qualitative research, researchers can see the views of parents in Simpen Kidul village, Balubur Limbangan sub-district, Garut district in dealing with their children who have been involved with social media. This parent’s view is indispensable for this study to measure how big the role of parents in supervising their children playing social media.The role of parents for underage children who play social media is very important, because parental education and supervision greatly influences children's behavior and development. Although the ways of parent’s to educate their children are different, the goal they want to achieve is that parent’s do not want their children to have, miscommunication, especially to become addicted to playing social media which will later have a negative impact on their children, not only harm the child, of course detrimental to parent’s as well.